2019
DOI: 10.1136/bmjopen-2019-032462
|View full text |Cite
|
Sign up to set email alerts
|

Household preparedness for emergency events: a cross-sectional survey on residents in four regions of China

Abstract: ObjectiveThis study aimed to assess household preparedness for emergency events and its determinants in China.DesignA cross-sectional questionnaire survey was conducted on 3541 households in China in 2015.ParticipantsHouseholds were selected using a stratified cluster sampling strategy, representing central, eastern, western and southern regions of China. The designed questionnaires were administered through face-to-face interviews.Outcome measuresHousehold emergency preparedness was measured with 14 indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 29 publications
4
24
1
1
Order By: Relevance
“…In particular, rural residents who had external reliant thinking were less focused on setting sub-floors while for those in the suburb it led to an underestimation of the importance of storing food and planning for evacuation. This result concurs with the findings of Chen et al (Chen et al 2019) and Grothmann and Reusswig (2006) that relying on external support leads households to disregard self-protective measures.…”
Section: Comparison Of Constraints Between Rural and Suburban Villagessupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, rural residents who had external reliant thinking were less focused on setting sub-floors while for those in the suburb it led to an underestimation of the importance of storing food and planning for evacuation. This result concurs with the findings of Chen et al (Chen et al 2019) and Grothmann and Reusswig (2006) that relying on external support leads households to disregard self-protective measures.…”
Section: Comparison Of Constraints Between Rural and Suburban Villagessupporting
confidence: 92%
“…2 Map of the study site et al 2018). Reliance on external support was reported to be negatively correlated with protective responses (Grothmann and Reusswig 2006;Chen et al 2019). In this study, household income was ranked by referring to the 2016-2020 living standard (Vietnamese Government 2015) and the 2017 report on the average income (GSO 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In today’s increasingly interconnected world, no community or country can be protected from public emergencies and disasters [ 1 ]. COVID-19 is a typical illustration of this.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research has suggested that household emergency preparedness can be affected by many factors such as knowledge, risk awareness and attitudes toward public health emergencies [ 1 ]. Some studies have also pointed out that people’s knowledge, attitude and practice (KAP), parts of their public health emergency response capability, play an important role in controlling the spread of an epidemic [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The factors associated with stockpiling for disasters (e.g., emergency kits) have been clarified in previous studies. For example, the associated factors were advanced age, male sex, higher income, and higher educational background [ 6 , 7 , 8 , 9 , 10 ] (i.e., socioeconomic status (SES) factors). However, although Japan has experienced many large disasters in the last 10 years, the improvement rate from 2011 (the year of the Great East Japan Earthquake) is only 6.4% [ 11 , 12 ] because there are many households that have never stockpiled food and also those whose stockpiling has been interrupted.…”
Section: Introductionmentioning
confidence: 99%